Police reorganization and crime: Evidence from police station closures - Sebastian Blesse; André Diegmann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2019)
Does the administrative organization of police affect crime? In answering this question, we focus on the reorganization of local police agencies. Specifically, we study the effects police force reallocation via station closures has on local crime. We do this by exploiting a quasiexperiment where a reform substantially reduced the number of police stations. Combining a matching strategy with an event-study design, we find no effects on total theft. Police station closures, however, open up tempting opportunities for criminals in car theft and burglary in residential properties. We can rule out that our effects arise from incapacitation, crime displacement, or changes in employment of local police forces. Our results suggest that criminals are less deterred after police station closures and use the opportunity to steal more costly goods.
Keywords: K42; R53; 330; Crime; Policing; Crime Deterrence; Police Station Closures